Antitussive Use in Patients with Inadequately Controlled Moderate-to-Severe Asthma: A Post Hoc Analysis of the Omalizumab EXTRA Trial - Rutland CJ; Iweala OI; Anders K; Ko J; Mital P; Gupta S; Mohan A (Journal of Asthma and Allergy, 2023)
Cedric J Rutland,1 Onyinye I Iweala,2 Kyle Anders,3 Jinnie Ko,3 Parul Mital,3 Sachin Gupta,3 Arjun Mohan4 1Rutland Medical Group, Newport Beach, CA, USA; 2Division of Rheumatology, Allergy, and Immunology, University of North Carolina, Chapel Hill, NC, USA; 3Genentech, Inc., South San Francisco, CA, USA; 4Division of Pulmonary and Critical Care Medicine, University of Michigan, Ann Arbor, MI, USACorrespondence: Sachin Gupta, Genentech, Inc., 1 DNA Way, South San Francisco, CA, 94080, USA, Tel +1 650-763-7791, Email Guptas71@gene.comAbstract: Acute and chronic cough are common symptoms in patients with severe allergic asthma. Although asthma-related cough can be controlled by asthma-specific medications, both prescription and over-the-counter antitussives are often also necessary. The anti-immunoglobulin E monoclonal antibody omalizumab is an effective treatment for patients with moderate-to-severe asthma, but little is known about subsequent antitussive use patterns. This post hoc analysis examined data from the Phase 3 EXTRA study that included patients aged 12– 75 years with inadequately controlled moderate-to-severe asthma. Baseline antitussive use was low overall (16/427, 3.7% for omalizumab and 18/421, 4.3% for placebo). Among patients with no baseline antitussive use (n = 411 omalizumab, n = 403 placebo), most patients (88.3% omalizumab, 83.4% placebo) reported not using antitussives during the 48-week treatment period. The percentage of patients using 1 antitussive was lower for patients treated with omalizumab than placebo (7.1% vs 13.2%), although the adjusted rate of antitussive use during the treatment period was similar for omalizumab and placebo (0.22 and 0.25). Non-narcotics were used more often than narcotics. In conclusion, this analysis found low use of antitussives in patients with severe asthma and suggests that omalizumab may have the potential to decrease antitussive use.Keywords: antitussive, asthma, cough, omalizumab